Imidazopyridine-Based 5-HT6 Receptor Neutral Antagonists: Impact of N1-Benzyl and N1-Phenylsulfonyl Fragments on Different Receptor Conformational States - Vanda, David; Canale, Vittorio; Chaumont-Dubel, Severine; Kurczab, Rafał; Satała, Grzegorz; Koczurkiewicz-Adamczyk, Paulina; Krawczyk, Martyna; Pietruś, Wojciech; Blicharz, Klaudia; Pękala, Elżbieta; Bojarski, Andrzej J; Popik, Piotr; et al. (Journal of medicinal chemistry, 2021)
G-protein coupled receptors (GPCRs) exist in an equilibrium of multiple conformational states, including different active states, which depend on the nature of the bound ligand. In consequence, different conformational states can initiate specific signal transduction pathways. The study identified compound 7e, which acts as a potent 5-hydroxytryptamine type 6 receptor (5-HT6R) neutral antagonist at Gs and does not impact neurite growth (process controlled by Cdk5). MD simulations highlighted receptor conformational changes for 7e and inverse agonist PZ-1444. In cell-based assays, neutral antagonists of the 5-HT6R (7e and CPPQ), but not inverse agonists (SB-258585, intepirdine, PZ-1444), displayed glioprotective properties against 6-hydroxydopamine-induced and doxorubicin-induced cytotoxicity. These suggest that targeting the activated conformational state of the 5-HT6R with neutral antagonists implicates the protecting properties of astrocytes. Additionally, 7e prevented scopolamine-induced learning deficits in the novel object recognition test in rats. We propose 7e as a probe for further understanding of the functional outcomes of different states of the 5-HT6R.
Keywords: molekulární konformace; Neurites; agonisté serotoninových receptorů; neurity; Animals; Astrocytes; Neuroprotective Agents; poruchy učení; Molecular Conformation; neuroprotektivní látky; vztahy mezi strukturou a aktivitou; neuroglie; mužské pohlaví; Rats; Rats, Sprague-Dawley; Humans; pyridiny; receptory serotoninové; Neuroglia; Receptors, Serotonin; Pyridines; Serotonin Receptor Agonists; Imidazoles; antagonisté serotoninu; lidé; zvířata; potkani Sprague-Dawley; receptory spřažené s G-proteiny; Receptors, G-Protein-Coupled; astrocyty; Serotonin Antagonists; krysa rodu Rattus; Learning Disabilities; imidazoly; Male; Structure-Activity Relationship